Performance Rating Analysis to Maximize the Working Time of Employees in The Packaging Department at a Soap Production Company - Mochamad Tutuk Safirin; Yekti Condro Winurseto; Rizqi Novita Sari; Mega Cattleya P. A. Islami (Future Science, 2022)
Performance rating is one of the work processes in which the process is identified, starting with the need for training and education, assigning people to jobs they can master, and maintaining fairness in salaries, benefits, promotions, recruitment, and dismissals. One of the soap production companies in Surabaya has several divisions in the division of its work process. The packaging section is the part that has the most employees in its operation, and its process requires more human labour. So that the work rhythm in the packaging section is considered very dense. As a result of these conditions, some workers feel complaints such as easy body aches, back pain, reduced concentration, and quick tiredness, which affects performance. In addition, some workers feel more unemployed than doing work. This study aims to determine the performance rating of the operators in the packaging division to maximize employee working time. The results show that the highest performance rating value for each operator is in the sorting, wrap, and packaging tasks section, with a performance rating value of 1.11 compared to other tasks.